Bioinspired facilitation of intrinsically conductive polymers: Mediating intra/extracellular electron transfer and microbial metabolism in denitrification. (May 2022) - Guo, Tingting; Lu, Caicai; Chen, Zhi; Song, Yuanyuan; Li, Haibo; Han, Yi; Hou, Yanan; Zhong, Yuan; Guo, Jianbo
Abstract: Intrinsically conductive polymers, polyaniline and polyaniline sulfonate (PASAni) were used to explore their effect on denitrification. Denitrification was accelerated 1.90 times by 2 mM PASAni and the possible mechanisms were mainly attributed to the accelerated electron transfer and the enhanced microbial metabolism activity. Intracellular electron transfer was accelerated by PASAni and the acceleration sites were from NADH to coenzyme Q (CoQ), quinone loop, from Complex II to CoQ and from QH2 to Cyt. c1 . Extracellular electron transfer was accelerated because PASAni promoted more secretion of redox species and PASAni embedded in extracellular polymeric substance (EPS). Moreover, PASAni itselfprovided more electron transfer pathways as redox species. Microbial metabolism activity was also enhanced by PASAni, which was reflected in the increased nitrate/nitrite reductase activity (236.13/155.43%), electron transfer system activity (112.49%), adenosine triphosphate level (133.41%) and EPS content (189.06%). Besides, the enriched Proteobacteria in PASAni supplement system was also conducive to denitrification. This work provided fundamental information for conductive polymers mediating microbial electron transfer and enhancing contaminants biotransformation. Graphical abstract: Image 1 Highlights: Denitrification was accelerated 1.90 times by 2 mM polyaniline sulfonate (PASAni). PASAni acted as electron carrier in intracellular electron transfer process. PASAni stimulated more redox species secretion for extracellular electron transfer. PASAni itself provided more electron transfer pathways as redox species. PASAni enhanced microbial metabolism activity.